A Systematic Review of Stimulant Use in Civilian and Military Aviation. Issue 3 (3rd July 2021) - Ehlert, Alex M.; Wilson, Patrick B.
ABSTRACT: Objective : To synthesize the observational data on stimulant use in civilian and military aviation. Background : Pilot fatigue is a major safety concern and effective countermeasures are crucial for sustaining flight performance. Stimulants are not recommended for routine use but can help sustain alertness and flight performance when the risk of fatigue is high. However, they may also elicit side effects. It is important to fully understand the contexts in which stimulants are used, including factors that contribute to their use and how aviators perceive them. Methods : A systematic literature search was conducted to identify observational studies on stimulant use specific to aviation tasks. Results : Caffeine was frequently used in civilian aviation, though prevalence of use and perceptions about efficacy depend on task demands and individual caffeine responses. Stimulant use in military aviation was dependent on several operational factors, including the duration and timing of operations, recent hypnotic medication use, and whether other fatigue countermeasures could be utilized. Military aviators generally viewed stimulants as beneficial and side effects were sparse and mild-moderate with a few exceptions. Notably, most studies identified were published over 10 years ago. Conclusion : Stimulant use is relatively common in aviation and many (but not all) aviators perceive them as beneficial, though more studies should be conducted in the modern aviation environment. Major side effects were rare, with a few exceptions.